Biosolid amendment of a calcareous, degraded soil in a semi-arid emvironment - Walter, I.=700 1 Martinez, F.; Cuevas, G.
(Es, En)
ilus., 28 ref.
Keywords: BIOMASA; PLANTAS DE COBERTURA; METALES PESADOS; PROPIEDADES FISICO-QUIMICAS SUELO; ESPAÑA